(untitled) (Annual of the Faculty of Philosophy in Skopje, 2015)
The system of protection and rehabilitation of persons with disability as well as the educational system in the Republic of Macedonia since year 2000 until today’s date has gone thru various changes caused by processes of non-institutional care and inclusion. Such changes has caused significantly decreasing the number of children with moderate intellectual disability in day care centers and Institution for rehabilitation of children and youth ((Topansko Pole ” and due to this change on the other hand we have domination of children with severe intellectual disability. Changing the structure of the beneficiaries, increasing the years of employment contract of the experts working with this children category and weak motivation is causing professional burn out. The research is conducted on a sample of 16 experts employed in the Institution for rehabilitation of children and youth Topansko Pole from Skopje and 94 experts employed in day care centers throughout the Republic of Macedonia. The experts hired for treatment of persons with severe intellectual disability in the Special Institution from Demir Kapija are with employment status for which is considered extended lasting, therefore the research is conducted with aim to observe if the experts covering this children category has needs of additional motivation and stimulation like implementing rewarded employment status as possibility for increasing the efficiency in working process and enhancing the quality of life of experts which are in direct and everyday contact with children with moderate and severe intellectual disability.